The Feats of the Knowers of God : (Manāqeb al-'ārefīn) - Aflākī, Shams al-Dīn Aḥmad-e (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
This is a 14th-century biography of the famous Persian mystic poet and 'Knower of God', Jalāl al-Dīn-e Rūmī, in the form of a large compendium of Sufi-style teaching stories. It was commissioned by a grandson about fifty years after Rūmī's death. The author-compiler, Aflākī, includes chapters on Bahā'-e Valad (Rūmī's father), Shams al-Dīn-e Tabrīzī (Rūmī's great love), Solṭān Valad and Amīr 'Āref (Rūmī's son and grandson), and other transmitters of the spiritual Heritage of the Mowlavī dervish order. The protagonists are portrayed as performing miracles and confronting critics and rivals. Circumstantial detail abounds, thus providing one of our few windows onto social and political life during the Saljūq and Mongol period in Asia Minor. The translation has an extensive index of persons and concepts to assist readers and students.